ARTISTS OF PAINTER VIKAS BHATTACHARYA, EMBODIED IN COLORS: रंगों में समाहित चित्रकार विकास भट्टाचार्यजी की कलाकृतियाँ - Shrivastava, Ruchika (International Journal of Research -GRANTHAALAYAH, 2014)
History of art is as old as human history. It is said that since the time when Manusya opened her eyes, from day to day he got involved in the task of new construction for his livelihood and this new creation trend has made his life exciting, happy and prosperous. To show this thrill, prosperity and prosperity, he (man) took the support of painting and made Ragas his companion to express it in the right form. He presented the darker colors and the lighter colors in front of those who saw them. Colors have a very important place in the life of any person. In modern surroundings, the arts have influenced human society in such a way that it feels incomplete without any kind of art, whether it is music, writing, photography or painting. In today’s context, in some ways, arts help to influence and highlight the personality of a person. What kind of effects can be shown by the use of veins in illustration in my written paper written by painter Bikas Bhattacharya ji, who are counted among photographers and painters, how will they use colors will remain the subject. कला का इतिहास उतना ही पुराना है जितना की मानव का इतिहास। ऐसा कहा जाता है कि मनुश्य ने जिस समय अपने नेत्रों को खोला तब से ही वह अपनी आजीविका के लिये दिन प्रतिदिन नव निर्माण के कार्य में जुट गया और उसकी इस नव निर्माण प्रवृति ने उसके जीवन को रोमांचक, खुषहाल व समृद्ध बनाया है। इस रोमांचकता, खुषहाली व समृद्धि को दर्षाने के लिये उसनें (मनुश्य नें) चित्रकला का सहारा लिया और उसे सही रुप में व्यक्त करने के लियें रगों को अपना साथी बनाया। उसने कहीं गहरे रंग तो कहीं हल्के रंगों का प्रयोग करके अपनी भावनाओं को देखने वालों के सम्मुख प्रस्तुत किया। रंग किसी भी व्यक्ति के जीवन में बहुत महत्वपूर्ण स्थान रखते है। आधुनिक परिवेष में कलाओं ने मानव समाज को इस तरह प्रभावित किया है कि वह किसी भी प्रकार की कला के बिना अपने आपको अधूरा महसूस करता है वह कला फिर चाहे संगीत हो, लेखन हो, फोटोग्राफी हो या फिर चित्रकला ही क्यों न हो। आज के परिवेष में कुछ प्रकार से कलायें व्यक्ति के व्यक्तित्व को प्रभावित व उजागर करने में सहयोग करती है। मेरे द्वारा लिखित षोध पत्र में चित्रण में रगों के प्रयोग से किस प्रकार के प्रभावों को दिखाया जा सकता है चित्रकार बिकास भट्टाचार्यजी जो फोटोयर्थाथ वादी चित्रकारों में गिने जाते है उन्होनें रंगों का किस प्रकार प्रयोग किया है यही विषय रहेगा।